Organic Supplements : Bodies and Things of the Natural World, 1580-1790 - Park, Julie, 1970-; Jacobson, Miriam Emma (Book collections on Project MUSE., 2020)
"This cross-disciplinary collection of essays examines the interlaced relationships between natural things and human beings in early modern and eighteenth-century Europe"--